Discrepancies in perception of fall risk between patients with subacute stroke and physical therapists in a rehabilitation hospital: a retrospective cohort study - Inoue, Seigo; Otaka, Yohei; Horimoto, Yukari; Shirooka, Hidehiko; Sugasawa, Masafumi; Kondo, Kunitsugu (Frontiers in Aging, 2023)
Abstract Objective: Falls are one of the most common complications of a stroke. This study aimed to clarify the discrepancy between the perceived fall risk of hospitalized patients with stroke and the clinical judgement of physical therapists and to examine the changes in discrepancy during hospitalization. Design: Retrospective cohort study Patients: This study included 426 patients with stroke admitted to a Japanese convalescent rehabilitation hospital between January 2019 and December 2020. Methods: The Falls Efficacy Scale-International was used to assess both patients' and physical therapists' perception of fall risk. The difference in Falls Efficacy Scale-International scores assessed by patients and physical therapists was defined as the discrepancy in fall risk, and its association with the incidence of falls during hospitalization was investigated. Results: Patients had a lower perception of fall risk than physical therapists at admission (p < 0.001), and this trend continued at discharge (p < 0.001). The discrepancy in fall risk perception was reduced at discharge for non-fallers and single fallers (p < 0.001), whereas the difference remained in multiple fallers. Conclusion: Unlike physical therapists, patients underestimated their fall risk, especially patients who experienced multiple falls. These results may be useful for planning measures to prevent falls during hospitalization.